N016 Is QUOTE-IBD a valid questionnaire for measurement of quality of care in IBD?. (16th January 2018) - Ljungström, E; Pihl Lesnovska, K; Fredrikson, M; Hollman Frisman, G; Hjortswang, H
Abstract: Background: The inflammatory bowel diseases (IBD) ulcerative colitis and Cohn's Disease are chronic and have negative effects on everyday life. 1 This makes quality of care crucial to achieve best health possible. 2 The questionnaire Quality of Care Through the Patient's Eyes-Inflammatory Bowel Disease (QUOTE-IBD) was the first published validated IBD-specific quality of care questionnaire. 3 The aim of this study was to validate the Swedish version of the QUOTE-IBD. Methods: QUOTE-IBD measures the importance and performance of various care aspects and the combined effect of the two as a quality impact score (QI). 3 Adult outpatients ( n = 400) at a gastroenterology clinic in the south-east of Sweden were asked to answer the questionnaire. Since there is no other existing questionnaire that measures the same aspects specifically for IBD as QUOTE-IBD, Visual Analog Scales (VAS 0–100 mm) were used for validation. VAS was also used as a proxy measure for the patient's global assessment of quality of health care. 3 Results: The response rate was 61% ( n = 234) and 56% answered every question in the questionnaire. The response rate for Performance was 62%, and the item non-response was up to 22%, while Importance was completely answered by 88%. All QUOTE-IBD dimensions (QI) correlated significantly ( p < 0.05) with their respective VAS (range r 's = 0.16–0.43), except for accommodation ( r 's = −0.02). Cronbach's alpha for the Performance part of the questionnaire was 0.86, and for Importance 0.89. Cronbach's alpha for the 13 IBD-specific questions was 0.78. Test–retest ( n = 32) for the QUOTE-IBD dimensions were significant ( p < 0.05) with a range r 's = 0.31–0.80, except for accommodation ( r 's = −0.15). Conclusions: The construct validity of the Swedish version of QUOTE-IBD is fairly good with a moderate reliability and good internal consistency. The high number of missing responses for Performance items may be related to the questions being too specific, which in turn can explain the moderate level of construct validity. References: 1. Pihl-Lesnovska K, et al . Patients' perspective of factors influencing quality of life while living with Crohn disease. Gastroenterol Nursing, 2010;33:37–44. 2. Elkjaer M, et al. IBD patients need in health quality of care ECCO consensus. J Crohn's Colitis, 2008;2:181–8. 3. van der Eijk I, et al. Quality of health care in inflammatory bowel disease: Development of a reliable questionnaire (QUOTE-IBD) and first results. Am J Gastroenterol, 2001;96 :3329–3336.